State of the World’s Indigenous Peoples - United Nations Department of Economic; Social Affairs (United Nations, 2025)
This sixth volume of the State of the World’s Indigenous Peoples focuses on the climate crisis, its impact on Indigenous Peoples, and the role Indigenous Peoples can and do play in mitigating the effects of climate change. It aims to provide a comprehensive overview of current and emerging issues in the context of the climate crisis from the perspective of Indigenous Peoples. Drawing on illustrative examples from across the seven sociocultural regions, the publication highlights both challenges and good practices linked to Indigenous Peoples’ experiences with and responses to the ongoing climate crisis. Ultimately, this report is intended to serve as an authoritative reference and advocacy tool for Indigenous Peoples and civil society organizations and to contribute to the broader conversation around climate change mitigation, adaptation and resilience.